Priority medical devices list for the COVID-19 response and associated technical specifications : interim guidance : 19 November 2020 (World Health Organization, 2020)
This document describes the medical devices required for the clinical management of COVID-19, selected and prioritized according to the latest available evidence and interim guidelines. This includes: oxygen therapy, pulse oximeters, patient monitors, thermometers, infusion and suction pumps, X-ray, ultrasound and CT scanners as well as personal protective equipment. In order to facilitate access to quality assured priority medical devices, the document also includes technical and performance characteristics, related standards, accessories and consumables. It is intended for policy-makers and planning officers in Ministries of Health, procurement and regulatory agencies, intergovernmental and international agencies as well as the medical device industry.
Keywords: Equipment and Supplies; Betacoronavirus; poskytování zdravotní péče; Delivery of Health Care; veřejné zdravotnictví; epidemický výskyt choroby; terapie; infekční lékařství; Disease Outbreaks; zdravotnické prostředky; COVID-19; Therapeutics